SUSTAINABILITY INNOVATION: DIGITAL MARKETING OF AGRIBUSINESS PRODUCTS FOR FARMERS - Muhamad Solekan; Nur Faisal, Herry; Rismarini, Rismarini (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Digital marketing allows farmers and agricultural suppliers to track and analyze market data and information in real-time. Farmers and agricultural suppliers can also create and manage effective digital marketing campaigns to promote their agricultural products. Digital marketing is a solution to overcome the problem of marketing agricultural products, where marketing channels are still relatively long, which can be detrimental to farmers as producers. Marketing plays a key role in increasing the added value of agribusiness products. Digital innovation in agribusiness has significant benefits in solving the problem of oversupply. This research in-depth investigates sustainability innovation: digital marketing of agribusiness products for farmers using a literature review approach. This research discusses digital marketing strategies for agribusiness products for farmers, marketing agricultural products through digital platforms, innovative marketing strategies in agribusiness and digitalization of agribusiness marketing in reducing oversupply of agricultural products.